Analisis Perubahan Karakteristik Agroklimat dan Produktivitas Padi pada Kondisi Triple Dip La Niña (2020 -2022) di Jawa Timur - Mira Fitria; Ajeng Utari Siti Saodah; Annisa Noyara Rahmasary; Deni Okta Lestari; Alfiah Rizky Diana Putri (LPPM Universitas Putera Batam, 2026)
East Java Province is one of the main rice producing provinces in Indonesia and plays an important role in supporting national food security. The El Niño Southern Oscillation (ENSO) phenomenon can affect agroclimatic characteristics through changes in rainfall, Wet Months (WM), and Dry Months (DM), which may affect rice production and productivity. This study aims to analyze the effect of the Triple Dip La Niña (2020–2022) on agroclimatic characteristics, rice production, and productivity in East Java by comparing it with the neutral ENSO condition in 2013. The data used include monthly Sea Surface Temperature (SST) data from the National Oceanic and Atmospheric Administration (NOAA), monthly rainfall data from the Climate Hazards Group InfraRed Precipitation with Station Data (CHIRPS), and monthly rice production and productivity data from Statistics Indonesia (BPS) East Java. The methods include SST anomaly calculation to identify ENSO phases, Oldeman classification to determine the WM DM classes, and temporal and spatial analyses of rice production and productivity. The results show that 2013 was a neutral ENSO period, while the Triple Dip La Niña lasted from August 2020 to January 2023. During this period, most areas of East Java were dominated by the WM3DM2 class, which supports a rice–rice cropping pattern with a Cropping Index (CI) of 2. Rice productivity remained relatively stable, ranging from 42 to 73 quintals/ha, while rice production varied among regencies due to differences in WM DM zoning, paddy field area, and the frequency of natural disasters. Therefore, the Triple Dip La Niña changed agroclimatic characteristics in East Java but did not significantly affect rice productivity.